Forms of direct democracy in the system of local self-government in foreign countries - Kondratovich, Natallia М. (Journal of the Belarusian State University. Law, 2022)
The article considers the forms of direct democracy in the system of local self-government in foreign countries: a local referendum, recall of an elected person, local elections, a meeting (gatherings) of citizens, a law-making initiative, a survey of citizens, an appeal of citizens, etc. Examples of legislative regulation and practical implementation of various forms direct democracy in the system of local self-government on the example of individual countries.
Keywords: local government; forms of local government; local referendum; recall of an elected person; local elections; meeting (gatherings) of citizens; lawmaking initiative; survey of citizens; appeal of citizens